PELAYANAN SEKOLAH UNTUK MENINGKATKAN KUALITAS PESERTA DIDIK - Asmi, Engla; Sahuri, Chalid (Jurnal Kebijakan Publik, 2013)
The research was carried out in theexisting SLTPN in District Kuantan Kuantan District Singingi Downstream, where the informantresearch is the principal, teachers, parents and prominent intellectuals. Data collected by interviewand observation techniques, after the data was collected and then analyzed using qualitativedescriptive analysis. The result showed that the services the school in improving the quality ofjunior high school students in Kuantan District Downstream been running pretty well. While thefactors found to influence school services in improving the quality of students in junior subKuantan Kuantan District Downstream Singingi is empathy factor.